A brainstorming flipped classroom approach for improving students' learning performance, motivation, teacher-student interaction and creativity in a civics education class. (December 2020) - Tsai, Meng-Ning; Liao, Yu-Fan; Chang, Yu-Lin; Chen, Hsueh-Chih
Highlights: A brainstorming flipped classroom approach was proposed. An experiment was conducted in a secondary school civics course. The approach increased the students' learning performance, creativity, and better teacher-student interactions, peer interactions. The approach helped teachers to design the meaningful classroom activities in-class time. Abstract: A flipped classroom approach is a teaching/learning strategy and mode in which the inclass direct teacher instructing and the out-of-class students homework are switched. Previous studies have mostly used undergraduates as their participants, less of them used K-12 students; and used flipped classrooms in the teaching of core subjects, while studies of the flipped classroom for humanities cultivation are few. The present study has develop a brainstorming flipped classroom approach for civics education, in which the design was that the students read the course content before class and then the teacher guided the class discussions with the 635 brainstorming approach. The present study recruited 56 junior high school students and implemented a quasiexperiment for a civics course over a period of 6 weeks; the experimental group used the brainstorming flipped classroom approach, and the control group used the direct teaching instruction approach. The results show that the flipped classroom can effectively increase the students' performance, learning motivation for civics, citizen participation, better teacher-student interactions, peer interactions, and creativity than the control group. While the students are still able to acquire the basic knowledge required for the civics course. The brain storming flipped classroom approach developed by present study is not only a help to teaching of civic education, but also provides a firm structure for course design and pre-class learning for the whole learning process. The 635 brainstorming flipped classroom approach has pedagogical use in teaching practice and can be applied in many subjects.